Funkcje handlu - spojrzenie porównawcze - Pilarczyk, Bogna; Sławińska, Maria (Wydział Prawa i Administracji UAM, 1992)
The subject matter of the article is a comparative analysis of selected approaches to the nature and functions of trade, published in Polish and German literature over the last decades. The basis for distinguishing those functions are the existing objective discrepancies between demand and supply or between the "types of activity" resulting from the position taken by trade between the production and consumption spheres. A point of reference for the analysis is the theory of trade, formulated in the Poznań circle by Professor Zb. Zakrzewski. Comparing various approaches to the functions of trade, the author distinguishes three groups of such functions: functions connected with commodity, functions connected with showing discrepancies in time and space and the remaining functions.
Functions of trade - a comparative view